Principales arvenses que influyen en el cultivo de frijol phaseolus vulgaris l. en la zona andina ecuatoriana. - Calderon Jaramillo, Kelly Mahite (Machala : Universidad Técnica de Machala, 2022)
The Andean Region is made up of three mountain ranges that cross Colombia. These are the Cordillera Occidental, Cordillera Central and Cordillera Oriental. It abounds in ecological diversity due to the varied changes in altitude. This mountain range is found in South America through Ecuador and in some South American countries. In the Ecuadorian Andean zone, also known as sierra, inter-Andean or highlands, it extends from north to south through the Andes, its minimum altitude is 1800m or lower, up to 6268m with the Chimborazo. Dry and tender beans are grown in different provinces such as Azuay, Bolívar, Cañar, Carchi, Cotopaxi, Chimborazo, Imbabura, Loja and Pichincha through associated systems or cultivation alone. The influence of weeds in the cultivation of beans (Phaseolus vulgaris, L), which has a short cycle, is complex because they are of high diversity and quantity. Weeds are classified into two types: monocotyledons (narrow-leaved) and dicotyledons (broad-leaved) in different families. Likewise, vines have a life cycle that is annual (A) that completes its cycle in one year or less; and perennial (P) that can live for many years. However, in the Andean region there are 29 species of weeds that accompany the bean crop, causing damage and losses in production and yield in tons per hectare (Tha-1). On the other hand, it was pointed out how they can have a beneficial influence, since there are species that do not have a negative influence on the crop.
La Región Andina comprende de tres cordilleras que atraviesan por toda Colombia. Estas son la Cordillera Occidental, Cordillera Central y Cordillera Oriental. En ella abunda la diversidad ecológica por los cambios de altitud que son variados. Esta cadena de montañas se encuentra en América del Sur atravesando por Ecuador y en algunos países sudamericanos. En la zona andina ecuatoriana también denominada como sierra, interandina o serranías se extiende de norte a sur por los andes, su altura mínima es de 1800m o menor, hasta los 6268m con el Chimborazo. Se cultiva el frejol seco y tierno en diferentes provincias como Azuay, Bolívar, Cañar, Carchi, Cotopaxi, Chimborazo, Imbabura, Loja y Pichincha que lo realizan mediante sistemas asociados o cultivo solo. La influencia de las arvenses en el cultivo de frejol (Phaseolus vulgaris, L) que es de ciclo corto, resulta complejo porque estas son de alta diversidad y cantidad. Las arvenses se clasifican en dos tipos: Monocotiledóneas (hoja angosta) y dicotiledóneas (hoja ancha) en diferentes familias. Así mismo, las arvenses tienen un ciclo de vida que anual (A) que completa su ciclo en un año o menos; y perenne (P) que pueden vivir muchos años. Sin embargo, en la región andina existen 29 especies de arvenses que acompañan al cultivo de frejol ocasionando daños y perdidas en la producción y rendimiento en toneladas por hectárea (Tha-1). Por otro lado, se puntualizó como puede influir a beneficio, ya que existen especies que no influyen en contra al cultivo.
Keywords: PHASEOLUS VULGARIS L; ECUADOR; ZONA ANDINA; FREJOL; PRODUCCIÓN; ARVENSES